Nars x co. nars x fishing rod - Azmi, Anis Hazira; Mohamad Amin, Aamir Ibrahiem; Sukri, Mohammad Sulaiman; Mohd Tadjuddin, Nur Arissa Adriana (2021)
This business plan will introduce NARS X co. which is commonly focused on higher-end fishing rods with new technology that will make customers stunned with our product. This puts the emphasis on truly buying local, a rapidly growing trend in upscale and middle income alike. NARS X co. is a small business enterprise who sells modern fishing rod located in Kuala Terengganu, Terengganu, Malaysia. A types of our business is partnership and was formed on 1st January 2021.The reason why we decide to do a business of modern fishing rod are because our main activity of business is fishing tools products and our target customer such fisherman and people who loves to go fishing wanted or demanding something new about their fishing rod, That’s give NARS X co. come out with the idea by transforming the traditional or normal fishing rod to modern fishing rod. Name of our product was NARS X Fishing Rod. The fishing rod we transform using high quality materials for the rod and adding some LED light and the bell on it so it will be much easier for fisherman to see while fishing during night and notice the fish when it comes. NARS X co. will offer our target market sustainable and carefully curated products such as modern fishing rods. We will be a practical choice for local people by carrying necessities and by performing needed products for fishing activities. We will draw from the surrounding areas as well by functioning as a unique fishing shop destination, where we will give out our best services to customers so they will experience excellent customer experience. In our business, there are 5 managers in our business namely General Manager, Administration Manager, Marketing Manager, Operational Manager and lastly Financial Manager. Each manager has their own roles and responsibilities to make sure our business runs smoothly in the future without having any problems.